Theophrastus of Eresus : sources for his life, writings, thought and influence. Commentary volume 4, Psychology (Texts 265-327) - Huby, Pamela M. (Philosophia Antiqua, 1999)
This volume forms part of the large international Theophrastus project started by Brill in 1992 and edited by W.W. Fortenbaugh, R.W. Sharples and D. Gutas . Together with volumes comprising the texts and translations, the commentary volumes provide a new generation of classicists with an up-to-date collection of the fragments and testimonia relating to Theophrastus (c. 370-288/5 B.C), Aristotle's pupil and successor as head of the Lyceum. This will be the fourth volume of commentary on Theophrastus of Eresus. Sources for his Life, Writings, Thought and Influence , and is on the psychological and epistemological material. It includes contributions by Dimitri Gutas on the Arabic passages, and Pamela Huby has covered the rest, including close study of the quotations given by Priscian of Lydia and the extensive but little known medieval Latin passages. Different approaches to the use of medieval material as evidence for Theophrastus' thought are discussed in the Introduction.